The Value of HBME-1 and Claudin-1 Expression Profile in the Distinction of BRAF-Like and RAS-Like Phenotypes in Papillary Thyroid Carcinoma - BAĞCI ÇULÇİ, PELİN (HUMANA PRESS INC, 2016)
This study compared the expression profile of HBME-1 and claudin-1 in 90 papillary thyroid carcinomas (PTCs) with respect to the tumor architecture and invasive growth as reflected in 46 BRAF-like, 31 non-invasive RAS, and 13 invasive RAS-like phenotypes. Individual tumors were given an expression score (max 300) by multiplying the percent positive tumor cells by the intensity score (range 0-3). The higher expression of HBME-1 and claudin-1 distinguished BRAF-like phenotype from RAS-like phenotype. The same correlation was also retained for both markers when comparing BRAF-like phenotype with non-invasive and invasive RAS-like phenotypes. The expression scores and positivity rates for both markers did not yield any statistical difference among BRAF-like PTCs. Except the higher positivity rate of HBME-1, invasive RAS-like tumors were not statistically different than their non-invasive counterparts with respect to the positivity rate of claudin-1 and the expression scores of both markers. A central lymph node dissection or selective lymph node sampling was available in 20 specimens. The absence of claudin-1 expression has not been a feature of lymph node metastasis in this series. Despite the limited number of nodal sampling, BRAF-like phenotype and claudin-1 positivity status have been considered the best determinants of positive predictive value and negative predictive value in the prediction of lymph node metastasis among variables, respectively. Adoption of the simplified architectural classification approach to PTCs showed distinct biomarker expression profile in this series; however, immunohistochemistry for HBME-1 and claudin-1 does not seem to be useful in the distinction of invasive RAS-like PTCs from their non-invasive counterparts. Given the overlapping molecular signatures within the RAS-like phenotype, further studies with additional biomarkers are still needed to identify distinct protein expression signatures of non-invasive RAS-like phenotype as this diagnostic category still remains a surgical diagnosis at this time.
Keywords: Papillary thyroid carcinoma; BRAF-like papillary carcinoma; RAS-like papillary carcinoma; Claudin-1; HBME-1; Lymph node metastasis; NIFTP; FOLLICULAR EPITHELIAL DYSPLASIA; CYCLIN D1; DIAGNOSIS; UNDEREXPRESSION; ASSOCIATION; PROTEINS; P27/KIP; MARKERS; CANCER; FAMILY